Предмет: Математика,
автор: Vredena78
15•(а-4)=42+8•(a-4)
(a+1)•18=36+12•(а+1)
(a+5)•7-54=(a+5)•4
17•(a-2)-36=19+(a-2)•12
Ответы
Автор ответа:
1
1)15*(а-4)=42+8*(а-4)
15а-60=42+8а-32
15а-8а=42-32+60
7а=70
а=70:7
а=10
2)(а+1)*18=36+12*(а+1)
18а+18=36+12а+12
18а-12а=36+12-18
6а=30
а=30:6
а=5
3)(а+5)*7-54=(а+5)*4
7а+35-54=4а+20
7а-4а=20-35+54
3а=39
а=39:3
а=13
4)17*(а-2)-36=19+(а-2)*12
17а-34-36=19+12а-24
17а-12а=19-24+34+36
5а=65
а=65:5
а=13
15а-60=42+8а-32
15а-8а=42-32+60
7а=70
а=70:7
а=10
2)(а+1)*18=36+12*(а+1)
18а+18=36+12а+12
18а-12а=36+12-18
6а=30
а=30:6
а=5
3)(а+5)*7-54=(а+5)*4
7а+35-54=4а+20
7а-4а=20-35+54
3а=39
а=39:3
а=13
4)17*(а-2)-36=19+(а-2)*12
17а-34-36=19+12а-24
17а-12а=19-24+34+36
5а=65
а=65:5
а=13
Vredena78:
спасибо . я уже забыла все . сейчас пойду дочке объяснять
Похожие вопросы
Предмет: Математика,
автор: сардар6
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: pal1960
Предмет: Қазақ тiлi,
автор: almbaevalibi25
Предмет: Математика,
автор: 3aupa